2008
DOI: 10.1523/jneurosci.5338-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Asymmetries in Visual Pathways Carrying S-Cone Signals in Macaque

Abstract: In the lateral geniculate nucleus of macaque, we recorded from neurons with substantial input from S-cones and found that, on several important dimensions, the properties of neurons that receive inhibitory input from S-cones ("SϪ") are quite unlike those of neurons that receive excitatory input from S-cones ("Sϩ"). First, the organization of chromatic inputs differs substantially: in Sϩ cells, S-cone signals were usually opposed by those of L-and M-cones; in SϪ cells, signals from L-cones were usually opposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
152
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(178 citation statements)
references
References 64 publications
24
152
1
1
Order By: Relevance
“…S1 and S2, this is typical of our entire sample of younger and older observers. These characteristics are also consistent with S-cone ON and OFF responses of single cells in the LGN and cortex of macaque monkeys (19). Fig.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…S1 and S2, this is typical of our entire sample of younger and older observers. These characteristics are also consistent with S-cone ON and OFF responses of single cells in the LGN and cortex of macaque monkeys (19). Fig.…”
Section: Resultssupporting
confidence: 84%
“…Recently, an S-cone OFF signal has been shown to provide input to a melanopsin-containing retinal ganglion cell (16). Although the retinal circuits originating from the S cones are controversial, it is known that their signals are carried by ganglion cell axons that project to distinct sublaminae (the koniocellular layers) in the LGN (17), which, in turn, project to cytochrome oxidase blobs in layers 2 and 3 of primary visual cortex (18,19).To characterize the temporal properties of putative S-cone ON and OFF pathways, we measured detection of stimuli along a tritan line, an axis of S-cone modulation, customized for each observer to increase or decrease S-cone excitation at equiluminance, such that the M and L cones receive constant stimulation (20). We found that the S-cone response to increments is faster than the response to decrements, but the latter response is even slower for older individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Det var inntil ganske nylig gjort så få funn av opponente celler med hemmende S-tappebidrag at en var begynt å tvile på om slike celler overhodet kunne spille noen rolle for fargekodingen, men det ser nå ut til at denne tvilen er ryddet av veien (Valberg et. al., 1986b;Dacey & Packer, 2003;Tailby et al, 2008). Celler med hemmende S-tappeinput skiller godt mellom stimuli langs en hvit-gul dimensjon, noe parvocellulaere og 'M-L' og 'L-M' opponente celler ikke kan. Celler med aktiverende S-tappebidrag kan skille stimuli langs en hvit-blå dimensjon.…”
Section: Med All Respekt For Helmholtz Må VI Tilføye At "Farger Verkeunclassified
“…Beyond the retina, cells that receive a strong S-cone input are predominantly found in the koniocellular layers of the LGN. Differences between geniculate cells with S-on input and those with S-off input have been found in their L/M cone inputs, in their sensitivity, in their susceptibility to adaptation and in their spatial resolution for achromatic modulation [8][9] . It is not known how the distinct signals of these S-on and S-off channels are maintained in the cortex.…”
Section: Bistratified Ganglion Cells S-off Ganglion Cellsmentioning
confidence: 99%